2018
DOI: 10.1021/acscatal.8b01759
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Hydration Governs the Stability of Sn-Beta during Continuous Glucose Conversion

Abstract: The stability of Sn-Beta for the continuous upgrading of hexoses is improved dramatically upon the addition of small amounts of water to the methanol/sugar reaction feed, despite water itself being an unfavourable solvent. Herein, the molecular level origin of this effect is investigated. Spectroscopic studies of the catalytic materials pre-, post-and during operation, with operando UV-Vis, 119 Sn CPMG MAS NMR, DRIFTS-MS, TGA, TPD/O-MS and porosimetry, are coupled to additional kinetic studies, to generate det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(103 citation statements)
references
References 56 publications
7
96
0
Order By: Relevance
“…4). As we recently demonstrated that loss of crystallinity and pore fouling are not important factors with respect to deactivation of Sn-Beta for glucose isomerisation in MeOH [18,19,21], different possible causes of deactivation must explain the lower stability observed at higher loadings of Sn.…”
Section: Effect Of Metal Loading Of Post-synthetic Materialsmentioning
confidence: 94%
See 2 more Smart Citations
“…4). As we recently demonstrated that loss of crystallinity and pore fouling are not important factors with respect to deactivation of Sn-Beta for glucose isomerisation in MeOH [18,19,21], different possible causes of deactivation must explain the lower stability observed at higher loadings of Sn.…”
Section: Effect Of Metal Loading Of Post-synthetic Materialsmentioning
confidence: 94%
“…to allow a systematic study to be performed in a relatively short period of time. Furthermore, utilising pure MeOH allows identification of which materials are intrinsically more stable to deactivation through the mechanisms we recently identified for Sn-Beta catalysis [21]. Catalyst particles of 63-75 µm were employed after pressing and sieving.…”
Section: Effect Of Metal Loading Of Post-synthetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of furanics, THA, 3-deoxy compounds, and retro-aldol products mirrorst he pathways catalyzed by Sn-containingz eolites at near 160 8C. [4b] The tuning of product distribution by water resembles recent discoveries of water [12] and alkali ion [13] effects at the active site of heterogeneous Sn IV catalysts under such industrially relevant conditions.…”
mentioning
confidence: 91%
“…Biomass production from carbon dioxide exceeds 100 10 12 kg per year, [1] with an average carbohydrate content of nearly 75 %( in addition to 20 %l ignin and5 %o ther compound classes). [2] Contraryt oo ther renewable biomass, carbohydrates are obtainable as cheap bulk chemicals.…”
mentioning
confidence: 99%